Virulence of Bordetella bronchiseptica: role of adenylate cyclase-hemolysin. - Gueirard, P (1993)
Bordetella bronchiseptica is a pathogen of laboratory, domestic, and wild animals and sometimes of humans. In the present study some characteristics of the virulence of B. bronchiseptica isolates of different origin were studied. All isolates had similar phenotypes, similar bacteriological characters, and synthesized adenylate cyclase-hemolysin, filamentous hemagglutinin and pertactin but not pertussis toxin. These isolates, however, differed in their ability to express dermonecrotic toxin and to cause a lethal infection, but no correlation was found with the human or animal origin of the isolates. The fact that the most virulent isolate did not express dermonecrotic toxin suggests that this toxin does not play an important role in the virulence of the bacteria in the murine model. After infection with virulent B. bronchiseptica a very early synthesis and a persistence of anti-adenylate cyclase-hemolysin and anti-filamentous hemagglutinin antibodies were observed in the sera of infected mice, suggesting a persistence of the bacteria or of its antigens. B. bronchiseptica adenylate cyclase-hemolysin was purified and was shown to be a major protective antigen against B. bronchiseptica infection. Furthermore, we showed that its immunological and protective properties were different from that of B. pertussis adenylate cyclase-hemolysin, confirming that Bordetella species are immunologically different.